The impact of Russia's import embargo on the EU countries' exports - Viktorija Skvarciany; Daiva Jurevičienė; Silvija Vidžiūnaitė (Economies, 2020)
Political unrest inevitably has consequences for a national economy. International trade in a globalised world has great importance for countries. Unfortunately, due to various political events, countries apply some restrictions to each other. In 2014, Western countries imposed sanctions on trade with Russia, due to the annexation of Crimea. As a response, Russia announced an embargo on importing of some goods from European and North American countries, as well as Australia. The current study investigates the economic impact on EU countries due to the mentioned embargo. The EU countries were grouped according to the average for 1998-2018 exports of products to Russia using a cluster analysis. After the clustering, the gravity model was employed to develop the equations representing the international trade between each cluster and Russia. Although Russia declared an embargo on countries associated with the same group of goods, the economic impact on their economies was different. This study has a couple of limitations. The research reflects only the impact of the embargo on exports regardless of some possible indirect effects; the study assesses the export of all sectors due to limited data; and because the restrictions are applied only to the food sector, the research shows only relative changes in exports.
Keywords: F01; F51; F62; 330; embargo; embargo impact on economy; international trade; political decisions; cluster analysis; gravity model